Efficiency and Effectiveness of Regional Expenditure Management in Realizing Sustainable Development: an Empirical Study of the Jayapura City Government - Allolayuk, Paulus K.; Giovania, Gian; Sesa, Pascalina V. S.; Imbiri, Yosua (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine and analyze the efficiency and effectiveness of regional expenditure management in realizing sustainable development in the Jayapura City Government. The research approach used is descriptive quantitative, which aims to systematically describe the relationship between the variables of efficiency, effectiveness, and the achievement of sustainable development. The research sample consisted of data on the realization of the Jayapura City Government's Regional Revenue and Expenditure Budget (APBD) for the 2019–2024 period. The data was obtained through a documentary study of budget realization reports, local government financial reports, and data from the Jayapura City Central Statistics Agency (BPS) for the same period. Data analysis was conducted using triangulation techniques to improve the validity and reliability of the research results. The results show that the ratio of regional expenditure efficiency and effectiveness has a positive relationship with sustainable development achievements. Although the level of efficiency is not yet fully optimal, improvements in the Human Development Index (HDI), life expectancy, and per capita expenditure indicate that regional budget management is becoming more adaptive and productive. In the social dimension, the effectiveness of education and health expenditure has been proven to increase the average length of schooling (RLS), expected length of education (HLS), and life expectancy (AHH). However, there are still inequalities in access between regions. From the economic dimension, the increase in per capita expenditure and the stability of people's purchasing power indicate a more inclusive growth direction, despite the pressure caused by the post-pandemic impact. Meanwhile, in the environmental dimension, the government's consistent provision of drinking water services reflects the success of policy interventions in the basic infrastructure and public services sector.  This study can contribute to strengthening the Value for Money theory in public financial management, emphasizing the importance of budget efficiency and effectiveness as key to achieving sustainable development. In addition, this study supports the principle of good governance as a prerequisite for fair public budget allocation and its impact on social welfare and environmental conservation. These findings can serve as a basis for local governments to evaluate fiscal policies and development planning, particularly to strengthen the integration of expenditure efficiency with the achievement of Sustainable Development Goals (SDGs) indicators at the city government level.